Treatment of anemia with darbepoetin alfa in systolic heart failure - Swedberg, Karl (2013)
BACKGROUND: Patients with systolic heart failure and anemia have worse symptoms, functional capacity, and outcomes than those without anemia. We evaluated the effects of darbepoetin alfa on clinical outcomes in patients with systolic heart failure and anemia. METHODS: In this randomized, double-blind trial, we assigned 2278 patients with systolic heart failure and mild-to-moderate anemia (hemoglobin level, 9.0 to 12.0 g per deciliter) to receive either darbepoetin alfa (to achieve a hemoglobin target of 13 g per deciliter) or placebo. The primary outcome was a composite of death from any cause or hospitalization for worsening heart failure. RESULTS: The primary outcome occurred in 576 of 1136 patients (50.7%) in the darbepoetin alfa group and 565 of 1142 patients (49.5%) in the placebo group (hazard ratio in the darbepoetin alfa group, 1.01; 95% confidence interval, 0.90 to 1.13; P=0.87). There was no significant between-group difference in any of the secondary outcomes. The neutral effect of darbepoetin alfa was consistent across all prespecified subgroups. Fatal or nonfatal stroke occurred in 42 patients (3.7%) in the darbepoetin alfa group and 31 patients (2.7%) in the placebo group (P=0.23). Thromboembolic adverse events were reported in 153 patients (13.5%) in the darbepoetin alfa group and 114 patients (10.0%) in the placebo group (P=0.01). Cancer-related adverse events were similar in the two study groups. CONCLUSIONS: Treatment with darbepoetin alfa did not improve clinical outcomes in patients with systolic heart failure and mild-to-moderate anemia. Our findings do not support the use of darbepoetin alfa in these patients. (Funded by Amgen; RED-HF ClinicalTrials.gov number, NCT00358215.).